Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Properti Dan Real Estate Yang Terdaftar Di BEI) - Imam Aji Santoso (UNIVERSITAS RAHARJA, 2023)
This study aims to determine the effect of profitability, leverage and firm size on firm value. Firm value is an indicator of financial performance for companies that go public. High corporate value will indicate high shareholder prosperity. This research was conducted on property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period. With the number of samples taken were 30 companies, so that a sample of 90 data was obtained. The sampling method in this study used purposive sampling. The analysis technique used in this study is panel data regression analysis assisted by the eviews 9 program. The results of this study indicate that the variables of profitability and leverage have a positive effect on firm value. Meanwhile, the variable firm size has a negative effect on firm value.